Associations between cigarette smoking and biliary tract cancer by anatomic subsite and sex: a prospective cohort study in Japan - Yingsong Lin; Sayo Kawai; Tae Sasakabe; Michiko Kurosawa; Akiko Tamakoshi; Shogo Kikuchi (Cancer Causes & Control, 2022)
Purpose Biliary tract cancer (BTC) has not been considered a tobacco-related cancer, largely because of inconclusive results from epidemiological studies. We herein evaluate the association between cigarette smoking and risk of death from BTC by anatomic subsite and sex using data from a large, prospective cohort study in Japan. Methods The present study included 97,030 Japanese individuals who were enrolled in 1988–1990 and followed until 31 December 2009. Cox proportional hazards regression models were used to estimate relative risks (RRs) and 95% confidence intervals (CIs) for the association of BTC with cigarette smoking, including smoking status, number of cigarettes smoked per day, and pack-years of smoking. Results During a mean follow-up of 16.2 years, we documented 484 deaths (187 from gallbladder cancers and 297 from cancers of other and unspecified biliary tract parts). After adjustment for sex, age, body mass index, alcohol consumption, and history of gallstones, current smokers had a higher risk of death due to BTC (RR = 1.35, 95% CI = 1.01–1.79) than never smokers. In the analyses by anatomic subsite, current smoking was associated with an increased risk of death from gallbladder cancer (RR = 1.89 95% CI = 1.19–3.02), whereas no evidence of an association was noted for cancers of other and unspecified biliary tract parts (RR = 1.10, 95% CI = 0.77–1.58). Moreover, mortality risk increased with an increasing number of cigarettes smoked per day and pack-years of smoking, particularly for gallbladder cancer in men. Conclusion Cigarette smoking is associated with an increased risk of death from BTC, particularly gallbladder cancer, in Japanese men.